SCIENTIFIC HERITAGE OF PROFESSOR S.A. MOROZ AND THE IMPLEMENTATION OF ITS IDEAS TO CONTEMPORARY GEOLOGICAL SCIENCE - Ivanik, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article describes the scientific, organizational and public activity of prominent Ukrainian scientist, head of department of general and Historical Geology of Geological Faculty of Taras Shevchenko National University of Kyiv, a famous geologist, stratigrapher, palentologist, Chevalier of the Order "For Merit" of third degree, doctor of geological-mineralogical sciences, professor S.A. Moroz. It reveals the contribution to the improvement and further development of Ukrainian and World geological science, philosophical analysis and philosophical knowledge. The trends of modern geological research related to the scientific heritage of the famous scientist are analyzed.